2000
DOI: 10.1103/physrevb.61.7589
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting photovoltaic response and photoluminescence for distinct porous silicon pore structures

Abstract: The photoluminescent ͑PL͒ emission and photovoltaic ͑PV͒ response of two distinctly structured ͑prepared͒ porous silicon ͑PS͒ surfaces are compared and contrasted. The PV response of a porous silicon structure consisting of a microporous framework on which is superimposed a nanoporous layer is distinct from that of the branched nanoporous silicon structure generated in an aqueous etch environment. The observed PV response for this hybrid morphology is clearly not dominated by the covering nanoporous structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Whereas PS fabricated from aqueous electrolytes consists of highly nanoporous branched structures, PS fabricated from nonaqueous electrolytes is comprised of open and accessible microporous structures (p-micropores 19 ) with deep, wide, well-ordered channels . Taking advantage of this distinction, Gole et al developed a procedure to form microporous structures with nanoporous sidewalls. These hybrid microporous/nanoporous structures display a dramatically different photovoltaic (PV) response versus either crystalline silicon or nanoporous PS generated using an aqueous etch procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas PS fabricated from aqueous electrolytes consists of highly nanoporous branched structures, PS fabricated from nonaqueous electrolytes is comprised of open and accessible microporous structures (p-micropores 19 ) with deep, wide, well-ordered channels . Taking advantage of this distinction, Gole et al developed a procedure to form microporous structures with nanoporous sidewalls. These hybrid microporous/nanoporous structures display a dramatically different photovoltaic (PV) response versus either crystalline silicon or nanoporous PS generated using an aqueous etch procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The development of devices based on the porous silicon PL, while a focus of considerable effort, has been slowed by (1) the inability to enhance and stabilize this PL for long periods and (2) the inability to obtain a low resistance contact to the PS surface as typical resistances are of the order kΩ→MΩ. In overcoming this primary limitation in the application of PS, we have demonstrated that the PL from nanoporous or hybrid macroporous-nanoporous PS structures can be greatly enhanced and stabilized through treatment with aqueous HC1/methanol solutions [17,19]. More recently, based on this PL enhancement, we have developed a technique for the selective patterned metallization of a porous silicon (PS) surface using the photoluminescent surface as a reducing agent [20].…”
Section: Porous Silicon Sensorsmentioning
confidence: 99%
“…The electrochemical etching of silicon in a variety of electrolytes can produce a bewildering multitude of sizes and shapes [6,7]. Pore sizes can be made to vary [8][9][10][11][12][13][14][15] from the 1-10 nm range [8] to sizes of the order of 3 µm [15] and mixtures of two pore types are possible [9,[16][17][18]. Porous silicon (PS) formed from the HF-based etch of a silicon wafer is characterized by an extensive visible photoluminescence (PL) which when excited by uv radiation displays a time dependent behavior resulting primarily from surface-based oxidation processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid samples were etched with a current density of 6 mA/cm2 for between 50 and 75 min. Using this procedure, pores approximately 1 µ m wide and 10 µ m deep were formed, well covered by a coating of nanoporous silicon 42,43 .…”
Section: Photoluminescence Characterizationmentioning
confidence: 99%